Numerical modelling of the southeastern Vombsänkan. Groundwater levels, water budget and changed groundwater recharge. - Täcklind,Johan (ISRN LUTVDG(TVTG-5191)/1-90/(2025), 2025)
Vombsänkan is one of the largest groundwater aquifers in Sweden, it can be divided into a southeastern part with a limestone aquifer and a northwestern part with an aquifer in soil. The limestone aquifer is confined, since it’s overlain by low-permeability soils. All wells for irrigation and municipal purposes are drilled into the limestone rock. The goal is to establish a hydraulic groundwater model for the southeastern Vombsänkan. The aquifer faces challenges related to climate change and population growth. A decrease in groundwater recharge is anticipated, accompanied by a potential increase in irrigation demand. A future climate is expected to lead to increased competition for freshwater resources. Permitted groundwater extractions will need to be re-evaluated, and additional permits may be required to address emerging challenges. The purpose of the groundwater model is to evaluate water balances and groundwater levels under present condition, and to project potential changes under future climate conditions. Climate scenarios RCP8.5 is used to consider the effect of changed groundwater recharge. The groundwater model is established based on a hydrogeological conceptual model, which serves as the foundation for the numerical model developed in GMS MODFLOW. The numerical model will be calibrated and verified to ensure an accurate representation of the actual aquifer. The limestone rock aquifer is bounded by the coastline, a ridge and fault zones. These establish the model's boundary conditions, with the coastline serving as a constant head boundary, and the ridge and fault zones functioning as impermeable boundaries. The soil profile is simplified into an upper permeable layer overlying a less permeable layer. Additionally, the limestone rock is simplified to be represented by a single layer. A cell system is adapted to these three material layers, additional zones are used to account for deviations within each layer. The model is calibrated and verified under steady-state conditions using observed groundwater levels from April 2018. The calibration involves an iterative procedure in which various parameter values are adjusted in the model until the calibration criteria are satisfied. The model is also verified under steady-state conditions against disturbed scenarios during the mid-season of 2016. Calibration results exhibit a high level of agreement between observed and simulated groundwater levels. The overall error within the model remains well below the calibration target of approximately one meter. The calibration reveals a pronounced sensitivity towards assigned value on the limestone rock. Minor adjustments in hydraulic conductivity have a significant impact on the calibration results. Both verifications result in small errors, well within the verification target. Three steady-state simulations have been conducted with groundwater withdrawals for municipal use and irrigation activities. What sets these simulations apart are the recharge conditions. Reduced groundwater recharge results in lowered groundwater levels and a redistribution of groundwater balances. The simulations indicate that climate scenarios have a substantial impact on the aquifer, potentially resulting in decreased groundwater availability. The model relies on multiple simplifications and assumptions, as a result, precise determination of groundwater levels under future climate scenarios remains uncertain. A less sensitive model could be achieved by subdividing the limestone into more layers. A more precise model could be developed by using a transient approach to capture demand driven extractions and other seasonal variations.
Keywords: Vombsänkan; groundwater recharge; MODFLOW; climate scenario